Lecture ready 3. Strategies for academic listening, note, taking, and discussion / Laurie, Frazier Shalle Leeming, Sarosy, Peg, Shalle Kathy Sherak - Frazier, Laurie Leeming, Shalle Sarosy, Peg Sherak, Kathy (2007)
Wew trends in marketing resarch, businnes ethics